The Effect of Interval and Intensity of Defoliation on the Dry Matter Production of Some Important Grass Species of Western Rajasthan - Dabadghao, Late P M; Roy, R Deb; Marwaha, S P (Annals of Arid Zone, 2016)
Studies on the effect of three intervals and three intensities of defoliation on dry matter production of Lasiurus sindicus Henr., Panicum antidotals Retz., Cenchrus ciliaris Linn and Cenchrus setigerus Vahl., were carried out at Central Arid Zone Research Institute. Jodhpur from 1959 to 1961. In L. Sindicus and C. setigerus 30 days interval gave significantly higher production irrespective of variation in annual rainfall. Similar results were observed in C. ciliaris and P. antidotale only in drought year. In favourable year, however, 20 days interval gave higher yields over either 30 or 10 days and significantly so in P. antidotals. Clipping at IS cm stubble height in L. Bindings gave maximum yield irrespective of the season. In P. antidotals and O. ciliaris increasing the clipping height beyond 10 cm had no special advantage either in favourable or in drought year. In O. sstigsf"UB, however, increasing the height of clipping had no significant advantage except in drought year. Interaction between Interval and intensity of clipping was significant only in L. Sindicus and P. antidotes. Clipping at 15 em st bble height, at an interval of 3(J days in the former and 20 days in favourable and 30 days in drought year in the latter species, was found to be the best management.